Correlative Atom Probe Tomography and Transmission Electron Microscopy Analysis of Grain Boundaries in Thermally Grown Alumina Scale. (4th February 2019) - Povstugar, Ivan; Weber, Juliane; Naumenko, Dmitry; Huang, Taihong; Klinkenberg, Martina; Quadakkers, Willem J.
Abstract: We employed correlative atom probe tomography (APT) and transmission electron microscopy (TEM) to analyze the alumina scale thermally grown on the oxide dispersion-strengthened alloy MA956. Segregation of Ti and Y and associated variation in metal/oxygen stoichiometry at the grain boundaries and triple junctions of alumina were quantified and discussed with respect to the oxidation behavior of the alloy, in particular, to the formation of cation vacancies. Correlative TEM analysis was helpful to avoid building pragmatically well-looking but substantially incorrect APT reconstructions, which can result in erroneous quantification of segregating species, and highlights the need to consider ionic volumes and detection efficiency in the reconstruction routine. We also demonstrate a cost-efficient, robust, and easy-handling setup for correlative analysis based solely on commercially available components, which can be used with all conventional TEM tools without the need to modify the specimen holder assembly.